KAJIAN KOTA SEMARANG MENUJU KOTA RAMAH LANSIA - Evi Widowati; Fafurida Fafurida; Galuh Nita Prameswari (Jurnal Riptek, 2018)
This research aims to describe the peoples opinion especially elderly towards WHO indicator for an elderly friendly city. The other purposes is giving a recommendation for local government to achieve a goal “elderly friendly city in 2030”. Therefore, the government could arrange a policy and programs to achieve that purpose. The recommendation obtained from KRL indicator description who never been seen before by the government. The research methods is quantitative descriptive with primary data base and purpossive sampling method. The research result show the first indicator of open space and building belongs to the category "very convenience and convenience" with the percentage is 27% which means included in the range of 25% -49% that is "orange". The second indicator is transportation of 22% which means below the range value <25%, it is belongs to "red". Third indicator is Housing, which is the percentage value is 30%. It is belongs to 25% -49%. that is "orange". Fourth indicator is Social Participation at 10% which means below 25% that is "red". Fifth indicator is reverence and inclusion / social involvement. Which the percentage is 11% and below the <25% is "red". Sixth indicator is civil participation and employment of 25%, which means it falls within the 25% -49% range of "orange". Seventh indicator is communication and information equal to 15% which means to enter in range value <25% that is "red". Eighth indicator is "community support and health services" of 18% which means it is included in the <25% value range that is "red". The description of Semarang City assessment of 8 indicators of elderly friendly city in accordance with WHO standards are 8 indicators / dimensions containing 95 variables are 5 indicators, namely the indicator 2,4,5,7 and 8 entered in "red" category that is 62,5% and entered in the category of "orange" ie indicators 1, 3 and 6 that is 37. 5%.